2020
DOI: 10.1002/jctb.6488
|View full text |Cite
|
Sign up to set email alerts
|

Main parameters influencing the design of photocatalytic reactors for wastewater treatment: a mini review

Abstract: The research in the heterogeneous photocatalysis to remove different types of pollutants in liquid phase has notably increased in the last years. The main objectives of the research dealing with photocatalysis were: (i) to shift the photoactivity of catalysts in the visible light range or to increase the degradation rate; (ii) the use of the artificial light sources (low pressure lamp, high pressure lamp, LEDs, and optical fibers) and solar light; (iii) photocatalysts recovering and deactivation; (iv) photorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 111 publications
(156 reference statements)
2
24
0
Order By: Relevance
“…The results confirm the occurrence of photocatalysis on the surface of NPs are mostly influenced by their charged ions and the pH of the solutions [18,24]. Thus, the charged ions and change in pH promoted the pollutant's stability, neutralization, agglomeration, and adsorption onto the photocatalyst surface [24]. The high acidic medium-efficiency can be attributed to the presence of negatively charged contaminants in the effluent, which were attracted and adsorbed onto the surface of the positively charged photocatalysts (TiO 2 , Z-TiO 2 and A-TiO 2 ) [21,24].…”
Section: Photocatalytic Degradation 221 Effect Of Ph On Photocatalsupporting
confidence: 72%
See 2 more Smart Citations
“…The results confirm the occurrence of photocatalysis on the surface of NPs are mostly influenced by their charged ions and the pH of the solutions [18,24]. Thus, the charged ions and change in pH promoted the pollutant's stability, neutralization, agglomeration, and adsorption onto the photocatalyst surface [24]. The high acidic medium-efficiency can be attributed to the presence of negatively charged contaminants in the effluent, which were attracted and adsorbed onto the surface of the positively charged photocatalysts (TiO 2 , Z-TiO 2 and A-TiO 2 ) [21,24].…”
Section: Photocatalytic Degradation 221 Effect Of Ph On Photocatalsupporting
confidence: 72%
“…In the basic or alkaline medium (pH 8-9), the degradation efficiency of 66%, 64%, and 63% was, respectively recorded for the TiO 2 , Z-TiO 2, and A-TiO 2 . The results confirm the occurrence of photocatalysis on the surface of NPs are mostly influenced by their charged ions and the pH of the solutions [18,24]. Thus, the charged ions and change in pH promoted the pollutant's stability, neutralization, agglomeration, and adsorption onto the photocatalyst surface [24].…”
Section: Photocatalytic Degradation 221 Effect Of Ph On Photocatalsupporting
confidence: 70%
See 1 more Smart Citation
“…In recent years, several studies reported on the design of solar photocatalytic reactors aiming at the treatment of wastewater [20][21][22][23][24]. In this concept, a rectangular staircase photocatalytic reactor (RSPR) under solar irradiation ( Fig.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…indicated that there are many critical objectives of the research dealing with photodegradation of pollutants, including extending the absorption of bulk TiO 2 into the visible region, switching the artificial light sources (low‐pressure lamp, high‐pressure lamp, and LEDs, etc .) into solar light, recovering the photocatalysts, and deactivation of photocatalysts, etc 2 . Especially, Sacco et al .…”
mentioning
confidence: 99%